STEM CELLS TEST - RECOMMENDATION OF ECVAM FOR CHEMICAL TESTING WITH CONSEQUENCE IN HEALTH RISK ASSESSMENT - CIORBA, Daniela (Studia Universitatis Babeș-Bolyai Ambientum, 2019)
The introduction of stem cells in environmental health studies could mean an important step in health risk assessment. It may be all the more important as we attend to increase the environmental influences to disease -associated epigenetic changes among adults, but especially for children. The assessment of health risk requires testing of environmental chemicals which they continued to need more time in animal studies. The stem cells -human models, increase the rate of testing, that does not require dose translation across species. Validation of environmental exposure will be done for very large interval data, for many chemicals or "chemicals cocktails" at much lower costs.